2017
DOI: 10.3389/fmicb.2017.00615
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling of Transcription Factors of Helicobacter pylori under Different Environmental Conditions

Abstract: Helicobacter pylori is a Gram-negative bacterium that colonizes the human gastric mucosa and causes peptic ulcers and gastric carcinoma. H. pylori strain 26695 has a small genome (1.67 Mb), which codes for few known transcriptional regulators that control bacterial metabolism and virulence. We analyzed by qRT-PCR the expression of 16 transcriptional regulators in H. pylori 26695, including the three sigma factors under different environmental conditions. When bacteria were exposed to acidic pH, urea, nickel, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 87 publications
1
38
0
Order By: Relevance
“…Given that several reports [20,21,[23][24][25][26][27] have previously described transcription levels of different proteins or virulence factors in response to H. pylori infection in vivo, and based on our results, we wanted to investigate if VapD expression occurs in gastric biopsies (in vivo) taken from patients with different severe gastric pathologies. We examined a total of 82 gastric biopsies: 41 from the gastric antrum and 41 from the gastric corpus from 41 patients with different diagnoses of cancer, peptic ulcer, follicular gastritis and chronic atrophic gastritis.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Given that several reports [20,21,[23][24][25][26][27] have previously described transcription levels of different proteins or virulence factors in response to H. pylori infection in vivo, and based on our results, we wanted to investigate if VapD expression occurs in gastric biopsies (in vivo) taken from patients with different severe gastric pathologies. We examined a total of 82 gastric biopsies: 41 from the gastric antrum and 41 from the gastric corpus from 41 patients with different diagnoses of cancer, peptic ulcer, follicular gastritis and chronic atrophic gastritis.…”
Section: Plos Onementioning
confidence: 99%
“…Studies have shown the expression of virulence factors, transcriptional regulators and different proteins of Helicobacter pylori under different developmental conditions [20,21]. However, there are no previous studies documenting the expression of VapD in H. pylori at the intracellular environmental level nor in gastric biopsies from patients with different gastric pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations have shown that H. pylori cells can grow as biofilm in vitro (Stark, Gerwig et al 1999, Yonezawa, Osaki et al 2010, Yonezawa, Osaki et al 2011, Servetas, Carpenter et al 2016, De la Cruz, Ares et al 2017, Hathroubi, Zerebinski et al 2018 as well as in vivo , Cammarota, Branca et al 2010) and make multicellular complex surface-attached communities. These studies suggest that biofilm formation may be a significant contributor to H. pylori persistence.…”
Section: Introductionmentioning
confidence: 99%
“…De la Cruz et al investigated whether a variety of stressors that H. pylori encounters in the stomach alters the expression of transcription factors as a mechanism to reprogram gene expression. 36 While most transcription factors did not show differential expression regardless of the conditions, there was marked increase in nearly all transcription factors during biofilm growth, and FliM was the most highly induced. As motility is downregulated during biofilm formation, the authors suggested that this points to the importance of FliM in regulating additional cellular processes.…”
Section: Transcriptional Regulatorsmentioning
confidence: 89%